2002
DOI: 10.1557/proc-754-cc3.3
|View full text |Cite
|
Sign up to set email alerts
|

In-plane Anisotropy in Hetero-Amorphous (CoFeB)-SiO2 Thin Films

Abstract: In order to engineer materials suitable for micromagnetic inductor cores we have fabricated and investigated the properties of granular (CoFeB)-SiO2 amorphous thin films. The deposition method, synchronous triple-rf magnetron sputtering onto rotating substrates, induces anisotropy in the film plane. Here we present magnetic hysteresis loops, resistivity and magnetoresistance measurements of two of these films, with different amount of metallic content. Both films have anisotropic resistivity, which is higher f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Since M r at T b < T < T sf is determined by a spontaneous magnetization of the SF phase, we may assert that the SF state preserves a homogeneous ferromagnetic order during the magnetization reversal, and no SF domains similar to described in [8,11,13] appear in the specimen. At the same time, no homogeneous magnetization of the film appears and demonstrates a decreasing angular dependence H C (ϕ) [17]).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Since M r at T b < T < T sf is determined by a spontaneous magnetization of the SF phase, we may assert that the SF state preserves a homogeneous ferromagnetic order during the magnetization reversal, and no SF domains similar to described in [8,11,13] appear in the specimen. At the same time, no homogeneous magnetization of the film appears and demonstrates a decreasing angular dependence H C (ϕ) [17]).…”
mentioning
confidence: 98%
“…Granular films (Co 0.25 Fe 0.66 B 0.09 ) 0.6 -(SiO 2 ) 0.4 about 500 nm in thickness were grown by magnetron sputtering [16,17]. The X-ray diffraction studies [17] showed that the granules are amorphous.…”
mentioning
confidence: 99%
See 1 more Smart Citation